Development of Learning Blocket Media for Vocabulary at A2 Level - Monica, Jeanita; Harahap, Herlina Jasa Putri (Asian Journal of Applied Education (AJAE), 2024)
The research aims to determine the process of making learning media using Blooket media for vocabulary learning and to describe the results of making learning media using Blooket for vocabulary learning. This research is a compilation study. This research uses the Richey and Klein model. There are three steps in this research, which are divided into three steps: (1) planning, (2) production, and (3) evaluation. The research results show that learning materials on the topic of family history were created using data collected from existing data sources during the research. Blooket's media about family history is packaged well, practical, interesting and effective so that students can easily understand the material and use it as a learning tool.